Studying the Spheromak Rotation in Data-constrained Coronal Mass Ejection Modeling with EUHFORIA and Assessing Its Effect on the B z Prediction - Ranadeep Sarkar; Jens Pomoell; Emilia Kilpua; Eleanna Asvestari; Nicolas Wijsen; Anwesha Maharana; Stefaan Poedts (The Astrophysical Journal Supplement Series, 2024)
A key challenge in space weather forecasting is accurately predicting the magnetic field topology of interplanetary coronal mass ejections (ICMEs), specifically the north–south magnetic field component ( B _z ) for Earth-directed CMEs. Heliospheric MHD models typically use spheromaks to represent the magnetic structure of CMEs. However, when inserted into the ambient interplanetary magnetic field, spheromaks can experience a phenomenon reminiscent of the condition known as the “spheromak tilting instability,” causing its magnetic axis to rotate. From the perspective of space weather forecasting, it is crucial to understand the effect of this rotation on predicting B _z at 1 au while implementing the spheromak model for realistic event studies. In this work, we study this by modeling a CME event on 2013 April 11 using the European Heliospheric Forecasting Information Asset. Our results show that a significant spheromak rotation up to 90° has occurred by the time it reaches 1 au, while the majority of this rotation occurs below 0.3 au. This total rotation resulted in poor predicted magnetic field topology of the ICME at 1 au. To address this issue, we further investigated the influence of spheromak density on mitigating rotation. The results show that the spheromak rotation is less for higher densities. Importantly, we observe a substantial reduction in the uncertainties associated with predicting B _z when there is minimal spheromak rotation. Therefore, we conclude that spheromak rotation adversely affects B _z prediction in the analyzed event, emphasizing the need for caution when employing spheromaks in global MHD models for space weather forecasting.